Penyuluhan tatap muka dan pemeriksaan PCR feses dalam meningkatkan pemahaman tentang koinfeksi kecacingan pada penderita HIV-AIDS kota Palembang - Ahmad Ghiffari; Chairil Anwar; Thia Prameswarie; Resy Asmalia; Ratika Febriani; Nadhea Yolanda; Faradila Faradila; Nurul Qamariah; Dalila Dalila; Sanely Risti (Fakultas Kedokteran Universitas Sriwijaya, 2026)
The co-infection of HIV with helminthiasis might accelerate the progression of HIV to AIDS, making a thorough comprehension of this condition essential for patients. This counseling session was conducted in the Ilir Timur 2 District (Dobu Coffee) with 30 HIV patients, employing a face-to-face methodology that included presentations by speakers and laboratory analyses of fecal materials. The comprehension was evaluated using a pre-test and post-test involving 34 participants, yielding an average pre-test score of 51.42 (standard deviation: 16.75) and a post-test score of 71.39 (standard deviation: 16.96), demonstrating a significant improvement. A PCR study indicated that 24 patients were positive for helminth infections. The results suggested a beneficial effect on participants' knowledge, but with score discrepancies. The detection of helminth infections in patients demands further investigation, including investigations on the correlation between helminth infections and the immune function of HIV patients. Additionally, routine examinations must be conducted as an integral part of patient health surveillance to guarantee beneficial early detection.